2003
DOI: 10.1172/jci200317601
|View full text |Cite
|
Sign up to set email alerts
|

Memory CD4+ T cells do not induce graft-versus-host disease

Abstract: Graft-versus-host disease (GVHD) remains a major cause of morbidity and mortality in allogeneic stem cell transplantation (alloSCT). Donor T cells that accompany stem cell grafts cause GVHD by attacking recipient tissues; therefore, all patients receive GVHD prophylaxis by depletion of T cells from the allograft or through immunosuppressant drugs. In addition to providing a graft-versus-leukemia effect, donor T cells are critical for reconstituting T cell–mediated immunity. Ideally, immunity to infectious agen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
87
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(93 citation statements)
references
References 32 publications
(17 reference statements)
4
87
0
2
Order By: Relevance
“…Studies of human-derived cells in humanized mice or GVHD model mice were performed using fluorescein isothiocyanateconjugated anti-HLA-A9 (OneLambda, Canoga Park, CA, USA) and anti-human lineage CD3, 14,16,19,20, and 56 (BioLegend, San Diego, CA, USA); phycoerythrin (PE)-conjugated anti-HLA A2 (BD Biosciences, San Jose, CA) and anti-CD56 (BioLegend); PE/cyanine (Cy) 5-conjugated anti-CD235ab (BD Biosciences); peridinin chlorophyll/Cy5.5-conjugated anti-CD8 (BioLegend); PE/Cy7-conjugated anti-CD3, anti-CD33 (BD Biosciences) and anti-CD38 (BD Biosciences); allophycocyanin (APC)-conjugated anti-CD3 (BioLegend) and anti-CD34 (BD Biosciences); APC/ Cy7-conjugated anti-CD19 (BioLegend); Pacific blue-conjugated anti-CD4 and anti-CD45 (BioLegend); and Alexa Fluor 405-or 647-conjugated anti-CD45 (BioLegend). Propidium iodide (PI, 1 mg/mL; Sigma-Aldrich, St. Louis, MO, USA) was added to samples to stain dead cells just before flow cytometric analysis.…”
Section: Flow Cytometric Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of human-derived cells in humanized mice or GVHD model mice were performed using fluorescein isothiocyanateconjugated anti-HLA-A9 (OneLambda, Canoga Park, CA, USA) and anti-human lineage CD3, 14,16,19,20, and 56 (BioLegend, San Diego, CA, USA); phycoerythrin (PE)-conjugated anti-HLA A2 (BD Biosciences, San Jose, CA) and anti-CD56 (BioLegend); PE/cyanine (Cy) 5-conjugated anti-CD235ab (BD Biosciences); peridinin chlorophyll/Cy5.5-conjugated anti-CD8 (BioLegend); PE/Cy7-conjugated anti-CD3, anti-CD33 (BD Biosciences) and anti-CD38 (BD Biosciences); allophycocyanin (APC)-conjugated anti-CD3 (BioLegend) and anti-CD34 (BD Biosciences); APC/ Cy7-conjugated anti-CD19 (BioLegend); Pacific blue-conjugated anti-CD4 and anti-CD45 (BioLegend); and Alexa Fluor 405-or 647-conjugated anti-CD45 (BioLegend). Propidium iodide (PI, 1 mg/mL; Sigma-Aldrich, St. Louis, MO, USA) was added to samples to stain dead cells just before flow cytometric analysis.…”
Section: Flow Cytometric Analysismentioning
confidence: 99%
“…We transplanted 1.0 Â 10 7 cells/mouse HLA-A2-negative or -positive PBMCs into NOG mice without irradiation (day 0). To judge whether GVHD had developed or not, blood tests, determinations of body temperature and weight, and assays of skin damage were used in previous studies [18][19][20]. In this study, to ensure as objective a determination of the onset of GVHD as possible, we decided to define GVHD onset based on minor changes in biomarker values, body temperature, and body weight, as in clinical settings (Fig.…”
Section: Xenogeneic Model Of Gvhd Treatment With Kashmabmentioning
confidence: 99%
“…Prior studies have demonstrated that GVHD-inducing alloreactivity is mediated primarily by naïve and possibly early memory T cells [29,30] and also may depend on ERK1/2 activation [31], which is important for IL-2 production [32]. Therefore, we developed an approach to assess VDR and p-ERK1/2 simultaneously, and examined the maturation stage dependence of VDR upregulation.…”
Section: Vdr Upregulation Is Associated With Erk1/2 Phosphorylation Amentioning
confidence: 99%
“…They also demonstrated that CD8 þ T cells were primed early by host dendritic cells [6,18]. Other studies reported that removing CD8 þ alloreactive T cells in experimental models significantly reduced both the severity and duration of tissue damage [19][20][21].…”
Section: Discussionmentioning
confidence: 94%